Extractive Spectrophotometric Determination of Promethazine Hydrochloride - B. PATIL, DILIP; CHAFLE, D.M. (Asian Journal of Chemistry, 2010)
Two simple, sensitive, rapid and accurate extractive spectrophotometric methods have been developed for the estimation of promethazine hydrochloride in tablet forms. In first method, absorbance of promethazine hydrochloride-Eriochrome black-T complex was measured at 520 nm (λmax). Second method is based on the formation of promethazine hydrochloride-calcon complex having maximum absorbance at 540 nm. The proposed methods were validated statistically and by recovery studies. The linearity was found to 1.2-10.5 and 2.0-14.0 μg/mL for first and second method, respectively.